2013
DOI: 10.21897/rmvz.149
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de tres tipos de presas vivas en la larvicultura de bagre blanco (Sorubim cuspicaudus)

Abstract: RESUMENObjetivo. Evaluar el efecto de diferentes presas vivas en la larvicultura de bagre blanco (Sorubim cuspicaudus). Materiales y métodos. Al inicio de la alimentación exógena de Sorubim cuspicaudus, se ofreció zooplancton producido en mesocosmos (T1), zooplancton silvestre (T2) y nauplios de Artemia (T3), en concentración de 10.000 zoop/L, dos veces al día, durante seis días. Se utilizaron 18 acuarios de cinco litros de volumen útil, con densidad de 25 Larvas/L, seis réplicas por tratamiento en un diseño a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 7 publications
0
3
0
12
Order By: Relevance
“…and Moinodaphnia sp.) [37], and 0.1 prey mL −1 (Brachionus plicatilis, Ceriodaphnia reticulata, Apocyclops dengizicus) [42]. The density of cladocerans used in this study (20 prey mL −1 ) was higher than those reported in previous studies, suggesting that a homogeneous distribution of prey must accompany a high density to reduce cannibalism because it reduces the period of searching for prey and increases predator-prey encounters.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…and Moinodaphnia sp.) [37], and 0.1 prey mL −1 (Brachionus plicatilis, Ceriodaphnia reticulata, Apocyclops dengizicus) [42]. The density of cladocerans used in this study (20 prey mL −1 ) was higher than those reported in previous studies, suggesting that a homogeneous distribution of prey must accompany a high density to reduce cannibalism because it reduces the period of searching for prey and increases predator-prey encounters.…”
Section: Discussionmentioning
confidence: 58%
“…This result indicates that the prey offered an adequate nutritional quality to the larvae and allowed them to acquire high resistance against handling and transport. Prieto-Guevara, et al [37] claimed that the stress resistance test allows the estimation of quality and viability of larvae according to the type of food used; thus, a best survival in this test indicates a better condition of the larva and therefore a better nutritional quality of the food offered in association with the management conditions. Atencio-García, et al [2] stated that stress resistance due to anoxia conditions for B. sinuensis larvae is a valuable tool for determining the animal's physiological status before being sent to the nursery ponds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Una posible solución para enfrentar esta barrera sobre la baja disponibilidad de semilla, es aumentar la sobrevivencia en la fase larvaria que se logra al determinar el tiempo de desarrollo, el tipo de alimento que consumen en su primera alimentación, sea productividad primaria presente en el agua o la suministrada en esta fase (Rønnestad et al, 2013;Portella et al, 2014); además de la cantidad de reservas vitelinas endógenas y los requerimientos nutricionales en los primeros días de vida de las larvas (Rodríguez, 2009;Maciel et al, 2010;Rønnestad et al, 2013;Portella et al, 2014;Prieto et al, 2015) en su primera etapa, de la disponibilidad de presas vivas (rotíferos o artemia) principalmente.…”
Section: Introductionunclassified
“…A pesar de ser un pez carnívoro (Villadiego et al, 2004), es una opción para diversificar la piscicultura colombiana, debido a su gran valor comercial, la calidad de su carne, buena adaptación al cautiverio, adecuada tolerancia al manejo y buena respuesta a los protocolos de reproducción inducida (Villadiego et al, 2004;Espinosa, 2013;Prieto-Guevara et al, 2013). Pese a los avances en su reproducción artificial, aún persisten dificultades para la producción a gran escala de alevinos; por lo que esta especie no se ha podido ofrecer como alternativa de cultivo por la carencia de una tecnología confiable de producción masiva de semilla (Espinosa, 2013).…”
Section: Introductionunclassified